Peculiarities of microbial exopolysaccharide ethapolan synthesis on mixed waste oils - Ivahniuk, Mykola; Voronenko, Andryi; Pirog, Tatiana (My University, 2018)
Possibility of the microbial exopolysaccharide (EPS) ethapolan (the producer − Acinetobacter sp. IMB B-7005) synthesis intensification on the mixture of waste oils of various types and quality, as well as the emulsifying properties of that EPS, synthesized in such conditions, were studied. Materials and methods. Cultivation of Acinetobacter sp. IМV B-7005 strain was performed in liquid medium, containing as a carbon source waste oils (sunflower, corn, olive) at concentration 5%, v/v. EPS concentration was determined gravimetrically after precipitation with isopropanol, EPS-synthesizing ability − as a ratio of EPS concentration to biomass concentration, wich was expressed as g EPS / g biomass. Results and discussions. Regardless of the oil type in the inoculum obtaining medium (olive or sunflower), the ethapolan synthesis indexes on the mixture of waste sunflower and olive oils (in the ratio of 1:4; 4:1; 1:1) were slightly lower than in conditions of the producer growth on refined sunflower oil, but at the same time increasing of the EPS-synthesizing ability on 14−41% was observed. Using mixed after frying meat, potatoes, onions and cheese sunflower oil as a substrate for the ethapolan production accompanied by the synthesis of the same polysaccharide concentration, as well as on refined oil. Reduction of the initial quantity of mixed sunflower oil to 1.25−2% with followed fractional adding in portions of 1.25−1.5% in the cultivation process to the final amount of 5% was accompanied by increase of ethapolan concentration on 15−20% compared to a one-time addition of 5% substrate. Solutions of the synthesized under such conditions polysaccharide at concentration of 0.05% emulsified hexadecane, gasoline, diesel fuel (emulsification index 48−52%), and the formed emulsion was stable for 20 days. Conclusion. The results demonstrate the possibility of universal technology creating for microbial exopolysaccharide ethapolan production on mixed waste sunflower oil, regardless of the substrate type and supplier. Можливість інтенсифікації синтезу мікробного екзополісахариду (ЕПС) етаполана (продуцент − Acinetobacter sp. IMB B-7005) на суміші відпрацьованих масел різного типу та якості, а також емульгуючі властивості цього ЕПС, синтезованого в таких умовах, були вивчені. Матеріали та методи. Культивування Acinetobacter sp. Штам IМV B-7005 проводили на рідкому середовищі, що містить як джерело вуглецю відпрацьовані олії (соняшникова, кукурудзяна, оливкова) у концентрації 5 % об./об. Концентрацію ЕПС визначали гравіметрично після осадження ізопропанолом, ЕПС-синтезуючу здатність − як відношення концентрації ЕПС до концентрації біомаси, яке виражали як г ЕПС / г біомаси. Результати та обговорення. Незалежно від типу олії в середовищі отримання інокулята (оливкова чи соняшникова) показники синтезу етаполану на суміші відходів соняшникової та оливкової олій (у співвідношенні 1:4; 4:1; 1:1) були дещо нижчими, ніж в умовах зростання продуцента на рафінованій соняшниковій олії, але при цьому спостерігалося підвищення ЕПС-синтезуючої здатності на 14−41%. Використання змішаної після смаження м’яса, картоплі, цибулі та сиру соняшникової олії як субстрат для виробництва етаполану, що супроводжується синтезом полісахаридів такої ж концентрації, як і на рафінованій олії. Зменшення вихідної кількості суміші соняшникової олії до 1,25−2 % з наступним дробовим додаванням порціями 1,25−1,5 % у процесі культивації до кінцевої кількості 5 % супроводжувалося підвищенням концентрації етаполану на 15−20 % порівняно з одноразове додавання 5% субстрату. Розчини синтезованого в таких умовах полісахариду концентрацією 0,05 % емульгували гексадекан, бензин, дизельне паливо (індекс емульгування 48−52 %), і утворена емульсія була стабільною протягом 20 діб. Висновок. Результати демонструють можливість створення універсальної технології виробництва мікробного екзополісахариду етаполану на змішаних відходах соняшникової олії незалежно від типу субстрату та постачальника.
Keywords: екзополісахариди; відпрацьована олія; культивування; емульгування; кафедра біотехнології і мікробіології; Acinetobacter sp. ІМВ В-7005; exopolysaccharide; waste oils; cultivation; emulsification